2018
DOI: 10.3400/avd.oa.16-00135
|View full text |Cite
|
Sign up to set email alerts
|

Early and Mid-Term Results of Endovascular Aortic Repair Using a Crossed-Limb Technique for Patients with Severely Splayed Iliac Angulation

Abstract: Objective: We evaluated early and mid-term results of endovascular aortic repair (EVAR) using crossed-limb and non-crossed-limb techniques.Material and Methods: From December 2011 to October 2013, 37 patients (31 men; mean age 75.4 years) were treated with EVAR (crossed-limb, 21 and non-crossed-limb, 16). We compared technical success, maximum short-axis diameter of abdominal aortic aneurysm, iliac angulation, time for catheterization of the short contralateral limb gate of the main body (SCT), and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The comparison showed an insignificant difference between the two techniques and rendered it safe to use on AAA patients [ 43 ]. Yagihashi et al [ 44 ] reported similar results in another investigation based on the early and midterm results of crosslimb and conventional EVAR techniques. The researchers considered EVAR technique to be safe for the treatment of all AAA cases including the severely splayed iliac angulation [ 44 ].…”
Section: Discussionmentioning
confidence: 63%
“…The comparison showed an insignificant difference between the two techniques and rendered it safe to use on AAA patients [ 43 ]. Yagihashi et al [ 44 ] reported similar results in another investigation based on the early and midterm results of crosslimb and conventional EVAR techniques. The researchers considered EVAR technique to be safe for the treatment of all AAA cases including the severely splayed iliac angulation [ 44 ].…”
Section: Discussionmentioning
confidence: 63%
“…5 Similar results were also observed in a study focusing on patients with severely tortuous iliac arteries. 6 However, both studies were subject to limited sample size, with a maximum of 27 CL patients. Results of the current largest cohort, involving 43 CL and 269 SL patients, indicated comparable outcomes except for a greater risk of type II endoleak (T2EL) in the CL group.…”
Section: Introductionmentioning
confidence: 99%
“…However solely deployment of the main body in crossed limb "ballerina" configuration does not decrease time of the cannulation [8,9].…”
Section: Discussionmentioning
confidence: 99%